AB0165 Regulation of Atherothrombosis in Systemic Lupus Erythematosus. Role of Different Monocyte Subsets, Netosis Involvement, and Effects of Anti-Dsdna Antibodies. (9th June 2015) - Perez-Sanchez, C.; Aguirre, M.; Galindo-Izquierdo, M.; Ruiz-Limon, P.; Barbarroja, N.; Jiménez-Gόmez, Y.; Segui, P.; Collantes-Estévez, E.; Cuadrado, M.; Lόpez-Pedrera, C.
Abstract : Background: Atherothrombosis in systemic lupus erythematosus (SLE) has been related to the combined effects of autoimmune elements and cells of the immune system, where monocytes play an essential role. Different monocyte subsets with distinct pathophysiological actions have been described in cardiovascular disease (CVD). Netosis suffered by neutrophils in SLE might further contribute to the development of inflammatory and thrombotic processes. Objectives: 1. To analyse in vivo the involvement of different monocytes subsets and netosis in the development of CVD in SLE patients. 2. To evaluate in vitro the role of anti-dsDNA antibodies in these processes. Methods: The study was conducted in 23 SLE patients and 10 healthy donors. Endothelial function was assessed by measuring the post-occlusive hyperaemia using Laser-Doppler. Monocyte subsets (MON1: CD14+/CD16-, MON2: CD14+/CD16+; MON3: CD14dim/CD16+) were characterized by flow cytometry. Classical (CD14 +) and non-classical (MON2/MON3, CD16 +) monocytes were purified using immuno-magnetic selection. Various markers of oxidative stress, inflammatory cytokines and prothrombotic mediators were quantified. In purified neutrophils, levels of oxidative stress and elastase were analyzed, as well as the percentage of netosis after labeling with Sytox. Purified neutrophils and monocytes from healthy donors were treated in vitro with anti-dsDNA antibodies isolated from the serum of SLE patients, and markers of inflammation, thrombosis, and oxidative stress were evaluated. Results: SLE patients showed impaired micro vascular endothelial function (reduction of hyperaemia post occlusion area) and increased plasma levels of pro-inflammatory proteins (IL6, IL8, MCP-1 and PCR). Percentage of MON2 was found increased and associated to the disease status (SLEDAI). Moreover, this monocyte subset showed an increase in TF, IKK and TNFα expression, and a decrease in intracellular glutathione (GSH) in relation to MON1. Increases in neutrophil elastase levels and the percentage of cells suffering netosis were also identified. Neutrophils further displayed altered mitochondrial membrane potential and a decrease in GSH. The increased percentage of MON2 and molecules related to inflammation and thrombosis, endothelial dysfunction, oxidative status and netosis were associated with the occurrence of thrombotic events, as well as with the presence of anti-dsDNA antibodies. In vitro treatment of monocytes and neutrophils with anti-dsDNA antibodies promoted an increase in the production of peroxides, various intracellular cytokines and proinflammatory and prothrombotic molecules. Conclusions: 1. In SLE patients, the CD16 + monocyte subtype –present in higher proportion than in healthy donors- is associated with disease activity, thrombosis development and endothelial dysfunction. 2. Positivity for anti-dsDNA antibodies is linked to an increase of atherothrombotic markers in SLE patients. 3. Anti-dsDNA antibodies, in vitro, modulate the expression of various molecules related to inflammation and thrombosis. Together, that data suggest the involvement of such autoantibodies on atherothrombosis development in SLE. Acknowledgements: Supported by CTS-7940, PI12/01511, SER. Disclosure of Interest: None declared